A percepção prosódica gráfica na leitura silenciosa de sentenças subordinadas ambíguas temporárias por surdos bilíngues LIBRAS/Português - SANTOS, Hercules Rodrigues dos (2021)
In this research, we investigated the perception of graphic prosodic marking through by means of the Brazilian Portuguese comma punctuation mark in subordinate sentences with temporary structural ambiguity by bilingual congenital deafs and monolingual listeners. We start from the assumption that the deafs would activate the syntactic-semantic information in the disambiguation of the target sentences, appropriating the implicit prosody of LIBRAS, projected by them mentally, within the proposals that state that the comma is a visual prosodic marker in the written text. (Cagliari, 1989; Pacheco, 2006) and Fodor's Implicit Prosody Hypothesis (1998, 2002, 2005). Furthermore, we tested the interaction of comma with other grammatical information for disambiguation and sentence comprehension within the prosody-syntax-semantic interface using Frazier's Late Closure and Weak Semantic Principle (1979) strategies and the predominance of reanalysis of linguistic input through of the Good-Enough Hypothesis of Christianson et al. (2001). Therefore, we applied the experiment to six individuals, three deaf bilinguals LIBRAS / Portuguese and three monolingual Portuguese language listeners, Brazilian citizens from the region of Baixo Tocantins (Igarapé-Miri and Abaetetuba) from Pará. We opted for a clipping that included teaching high school (HS), undergraduate students (US) and active teachers (AT), to provide different levels of literacy of the subjects in the sample. Thus, we employed a self-monitored reading experiment with replicated materials by Ribeiro (2004), Fonseca (2012) and Carvalho (2016) under the conditions of Late Closure and Semantic Control with and without comma. The results indicated that the deafs perceived the comma in the silent reading of temporary ambiguous subordinate sentences. Additionally, we identified interaction between syntactic-prosodic-semantic components by bilingual deaf people in solving syntactically ambiguous sentences. In this sense, the silent reading time of Semantic Control sentences were longer for both deaf and hearing, while in Late Closure and with-comma versions were shorter for both groups, suggesting that the deafs are guided by general syntactic principles. However, in the overall comprehension of sentences, deaf people presented more difficulties of comprehension in comma-free Late Closure sentences than listeners, indicating inconsistency during processing.